Development and Testing of a Question Prompt List for Common Hand Conditions: An Exploratory Sequential Mixed-Methods Study - Satteson, Ellen S. (J Hand Surg Am, 2020)
PURPOSE: A question prompt list (QPL) is a tool that lists possible questions a patient may want to ask their surgeon. Its purpose is to improve patient-physician communication and increase patient engagement. Although QPLs have been developed in other specialties, one does not exist for hand conditions. We sought to develop a QPL for use in the hand surgery clinic using a mixed-methods design. METHODS: We drafted a QPL based on prior work outside of hand surgery and then used an exploratory sequential mixed-methods design (both qualitative and quantitative methods) to finalize the QPL. Qualitative evaluation included both a written questionnaire completed by a patient advisory board, hand therapists, and hand surgeons, as well as cognitive interviews conducted with clinic patients using the tool. Revisions to the QPL were made after each phase of qualitative analysis. The final QPL was then evaluated quantitatively using the system usability score (SUS) questionnaire to assess its usability. RESULTS: A patient advisory board consisting of 6 patients, 5 hand therapists, and 6 hand surgeons completed the written questionnaire. Thirteen patients completed a cognitive interview of the QPL. We completed a content analysis of the qualitative data and incorporated the findings into the QPL. Twenty patients then reviewed the final QPL pamphlet and completed the SUS questionnaire. The resulting SUS score of 78.8 indicated above-average usability of the QPL tool. CONCLUSIONS: The QPL developed in this study, from the perspective of multiple stakeholders, provides a usable tool to engage and prompt patients in asking questions during their visit with their hand surgeon with the potential to improve communication and patient-centered care. CLINICAL RELEVANCE: This study provides clinicians with a QPL developed for use in the hand surgery clinic setting, aimed at facilitating more thorough patient-provider discussion.